Preparation, characterization, and application of a valine-malonic acid based-DES as a potent catalyst for the green synthesis of thiazolopyrimidines - Nastaran Dehnokhalaji; Davood Habibi; Arezo Monem; Afagh Ranjbaran (Scientific Reports)
Abstract Based on the eutectic point phase diagram, a novel natural deep eutectic solvent (VAL/MAL-DES) was prepared by a mixture of one mole of valine (VAL) and one mole of malonic acid (MAL), and characterized by the eutectic points, FT-IR, 1HNMR, TGA/DTA and densitometer techniques. Then, it was used as a novel and capable catalyst for the green synthesis of thiazolo[3,2-a]pyrimidines via a one-pot four-component condensation reaction of 4-hydroxycoumarin, 2-amino-6-methylbenzothiazole, morpholine, and aldehydes at 80 °C with high yield and short reaction time.